Integrating Community Work Models into Social Work Interventions for Gender-Based Violence in South Africa: Considerations for Policy, Education, and Practice - Daniel Tuelo Masilo (Baileo: Jurnal Sosial Humaniora, 2026)
Gender-based violence (GBV) against women and girls remains a persistent social and public policy challenge in South Africa despite extensive legislative reforms and intervention programmes. Existing social work responses have predominantly focused on individual and remedial interventions, with limited attention to the integration of community-based approaches that address the structural and socio-cultural dimensions of GBV. This paper examines how community work models can be systematically integrated into social work interventions to strengthen GBV prevention and response mechanisms in South Africa. Employing a desktop study methodology, the paper draws upon an extensive thematic review of scholarly literature, government reports, policy documents, and other credible sources related to community work, gender-based violence, and social work practice. Guided by the ecosystem perspective, the analysis explores five community work models—community education, community development, social marketing, social planning, and social action—and evaluates their relevance for enhancing social work interventions across policy, education, and practice domains. The findings demonstrate that integrating community work models offers a comprehensive and multi-level framework for addressing GBV by promoting community participation, social transformation, preventive interventions, and survivor-centred support systems. The novelty of this paper lies in its conceptual integration of community work models into social work practice for GBV interventions within the South African context, providing an ecosystem-informed framework that extends beyond conventional case-based approaches. The paper concludes that community-oriented social work interventions are essential for addressing the structural determinants of GBV and advancing sustainable social change. It further recommends the incorporation of community work models into social work policy frameworks, professional education curricula, and practice guidelines. The proposed framework contributes to sociological scholarship by enriching theoretical understandings of the relationship between social structures, community agency, and collective responses to gender-based violence.